Impact of stress hyperglycemia mediating tissue-level collaterals on futile recanalization in large vessel occlusion patients - Li, Xinyu; Fu, Junling; Huang, Liping; Liu, Jin; Jiang, Shuyu; Wang, You; Gong, Chen; Xu, Tao; Chen, Yangmei (Frontiers in Endocrinology, 2025)
BackgroundThe stress hyperglycemia ratio (SHR) is associated with unfavorable functional outcomes in patients with large vessel occlusion. The potential effect of SHR on tissue-level collaterals (TLC) and futile recanalization is not clear.MethodsThis is a multicenter retrospective cohort study of patients with consecutive acute ischemic stroke due to large vessel occlusion (AIS-LVO) receiving endovascular treatment (EVT). The included patients had baseline glucose/HbA1c measurements and underwent cerebral perfusion imaging. TLC were measured using the hypoperfusion intensity ratio (HIR) [the volume ratio of brain tissue with (Tmax > 10 s/Tmax > 6 s)]. SHR was calculated as blood glucose (mmol/L)/[1.59 × HbA1C (%) − 2.59]. Using multivariable regression and mediation analyses, we determined the association among SHR, the TLC status, and futile recanalization (90-day modified Rankin Scale scores 3–6 despite successful recanalization).ResultsA total of 246 patients met the inclusion criteria. Patients in the highest tertile of SHR were significantly more likely to suffer futile recanalization compared with those in the lowest tertile [adjusted OR (aOR) = 3.56, 95%CI = 1.73–7.30, p < 0.001]. The TLC (aOR = 3.38, 95%CI = 1.23–9.27, p = 0.018) was worse in patients with elevated SHR and also acted as an independent predictor of futile recanalization (aOR = 2.31, 95%CI = 1.32–4.05, p = 0.003). Mediation analyses showed that the increased SHR was associated with worse TLC, accounting for 9.7% (95%CI = 1.9%–28.0%) of the harmful effect on futile recanalization. Mediation analyses also indicated a partial mediation effect of the baseline larger ischemic core (effect value = 13.5%, 95%CI = 3.1%–32.0%).ConclusionAn increased SHR is correlated with unfavorable TLC and is associated with futile recanalization after EVT. Future prospective studies should independently validate our findings.